Meningkatkan Efektivitas Antrian Pada Barbershop Dengan Menggunakan Cutman : Penyedia Jasa Booking Barbershop Berbasis Web - FADLY RAMDHANI; Alif Fadhlan Fadhilah (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2024)
Barbershop is now widely recognized in the community. Often people are annoyed by the queues that are full and long waits. Cutman is a web-based application that allows customers to book from home and can choose the time and also choose a haircut that suits the customer at Cutman Barbershop. In this way the customer can access the website, then the customer can make a booking by selecting the time and also the haircut. The Cutman application is designed using Visual Studio code (Vscode), PHP, HTML, Java script, and MySQL. This study uses a Likert scale. With this website, it can help customers in ordering shaving services online.